A highly efficient and stable catalyst for liquid phase catalytic exchange of hydrogen isotopes in a microchannel reactor. (23rd June 2021) - Fu, Qian; Xin, Feng; Yin, Xiaohong; Song, Yuexiao; Xu, Yongsheng
Abstract: The liquid phase catalytic exchange of hydrogen isotopes is a promising process for upgrading recycle water in nuclear power station. To facilitate the isotope catalytic reaction, a series of two-dimensional hydrophobic catalysts of Pt/modified carbon nitride (Pt/s-C3 N4 ) with different Pt loadings were fabricated and applied in microchannel reactor. Their excellent catalytic performances were found in our experiments by comparing with purchased Pt/activated carbon (Pt/AC), the Turn-Over-Frequency (TOF) of Pt/s-C3 N4 is 3 times higher than Pt/AC. Because the Pt clusters of 0.82 ± 0.08 nm were uniformly distributed on the support of two-dimensional carbon nitride (C3 N4 ) to improve availability of the Pt catalyst by exposing more active sites and decreasing effect of the internal diffusion. The catalytic activity of Pt/s-C3 N4 catalysts remained stable after 1800 min reaction, whereas Pt/AC displayed a 20% drop. Hydrophobicity of the catalyst maintained its high activity and stability in the liquid phase catalytic exchange reaction. Graphical abstract: Image 1 Highlights: Pt clusters of 0.82 nm were distributed evenly on carbon nitride by photochemical solid-phase reduction method. The wetting property of catalyst was improved to 144.5° by grafting PDMS onto support. The TOF of Pt/s-C3 N4 was 3 times higher than that of purchased Pt/AC in hydrogen isotope exchange reaction. Cycle tests proved high stability of Pt/s-C3 N4 in LPCE.